Nursing Roles In The Professionalism Of Health Careers In Ecuador - Cordero Pincay, Fernando (2025)
The objective of this review article is to compare the degree of professionalism exhibited by nurses in healthcare careers in Ecuador. The methodology employed in this study utilizes a qualitative approach with a descriptive scope. The design of the study was informed by a systematic review of 12 scientific articles obtained from the MyLOFT UCV virtual library, as well as scientific journals from websites such as PubMed, ProSciences, SCIELO, Scopus, and EBSCO. The four roles of nursing as a profession were considered: care, administration, research, and teaching. The results of the study indicated that most of the studies employed a descriptive qualitative approach, wherein researchers conducted bibliographic reviews on the professionalism of nurses. It has been determined that nursing professionals determine the timing of their execution of the four roles constituting their graduate profile, while maintaining a sense of relevance. The barriers that formerly limited the development of nursing professionals' competencies are now being dismantled through the implementation of a professional approach. A re-evaluation of the nursing curriculum is imperative in both public and private institutions, with the objective of enhancing pedagogy and administration competencies. This re-evaluation should be grounded in the contemporary framework of health systems.